Angioarchitecture of the hind foot in camel - JAIN, R K; DHINGRA, L D; NAGPAL, S K (The Indian Journal of Animal Sciences, 2013)
The blood supply to the hind foot of camel was carried through the branches of the third plantar common digital artery which bifurcated into the third and fourth plantar proper axial digital arteries. The third and fourth plantar proper axial digital arreries despatched the third and faurth plantar proper abaxial digital arteries respectively.